Finding Missing Cross-Language Links in Wikipedia - Moreira, Carlos Eduardo M.; Moreira, Viviane P. (Journal of Information and Data Management, 2013)
Wikipedia is a public encyclopedia composed of millions of articles written daily by volunteer authors from different regions of the world. The articles contain links called cross-language links which relate corresponding articles across different languages. This feature is extremely useful for applications that work with automatic translation and multilingual information retrieval as it allows the assembly of comparable corpora. Thus, it is important to have a mechanism that automatically creates such links. This has been motivating the development of techniques to identify missing cross-language links. In this article, we present CLLFinder, an approach for finding missing cross-language links. The approach makes use of the links between categories and of the transitivity between existing cross-language links, as well as textual features extracted from the articles. Experiments using one million articles from the English and Portuguese Wikipedias attest the viability of CLLFinder. The results show that our approach has a recall of 96% and a precision of 98%, outperforming the baseline system, even though we employ simpler and fewer features.